An integrated trauma-informed, mutual aid model of group work. Issue 3 (2nd July 2020) - Rosenwald, Mitchell; Baird, Jennifer
ABSTRACT: This article presents an integrated trauma-informed, mutual aid model of group work. It applies the concepts and evidence of the trauma-informed care movement in mental health to the group work model of mutual aid. Implications for social work practice, education, research, and theory-building are forwarded.